Outcomes of the six-strand M-Tang repair for zone 2 primary flexor tendon repair in 54 fingers. (June 2017) - Zhou, X.; Li, X.R.; Qing, J.; Jia, X.F.; Chen, J.
We repaired complete divisions of flexor tendons in zone 2 in 54 fingers using a six-strand core M-Tang repair method. Partial active digital motion started with early passive digital motion carried out first in the first 3–4 weeks after surgery and full range of active motion in later weeks. The patients were followed for 4–27 months. According to Strickland criteria or Tang criteria, 24 (83%) had excellent or good, four fair and one poor results in 28 fingers with follow-up of more than one year. In the other 25 fingers which were followed for less than 12 months, 19 (76%) had excellent and good, four fair and two poor results. There were no repair ruptures. We analysed outcomes against ages, gender, pulley integrity, accompanied injuries and follow-up times. The patients younger than 37 years old, male patients and with their A2 pulley(s) vented there were significantly better outcomes. The patients with longer than one year follow-up had significantly smaller extension deficits than those with less than one year follow-up. Level of evidence: IV